Sortase A Mediated Bioconjugation of Common Epitopes Decreases Biofilm Formation in Staphylococcus aureus - Kumari, Poonam; Nath, Yutika; Murty, Upadhyayula Surayanarayana; Ravichandiran, Velayutham; Mohan, Utpal (Frontiers in Microbiology, 2020)
Staphylococcus aureus is one of the most notorious pathogens and is frequently associated with nosocomial infections imposing serious risk to immune-compromised patients. This is in part due to its ability to colonize at the surface of indwelling medical devices and biofilm formation. Combating the biofilm formation with antibiotics has its own challenges like higher values of minimum inhibitory concentrations. Here, we describe a new approach to target biofilm formation by gram positive bacteria. Sortase A is a transpeptidase enzyme which is responsible for tagging of around ~22 cell surface proteins onto the outer surface. These proteins play a major role in the bacterial virulence. Sortase A recognizes its substrate through LPXTG motif. Here, we use this approach to install the synthetic peptide substrates on S. aureus. Sortase A substrate mimic, 6His-LPETG peptide was synthesized using solid phase peptide chemistry. Incorporation of the peptide on the cell surface was measured using ELISA. Effect of peptide incubation on Staphylococcus aureus biofilm was also studied. 71.1% biofilm inhibition was observed with 100µM peptide while on silicon coated rubber latex catheter, 45.82% inhibition was observed. The present work demonstrates the inability of surface modified S. aureus to establish biofilm formation thereby presenting a novel method for attenuating its virulence.